Crystal Structure of Carboxyltransferase from Staphylococcus aureus Bound to the Antibacterial Agent Moiramide B - Silvers, Molly A. (Biochemistry, 2016)
The dramatic increase in the prevalence of antibiotic-resistant bacteria has necessitated a search for new antibacterial agents against novel targets. Moiramide B is a natural product, broad-spectrum antibiotic that inhibits the carboxyltransferase component of acetyl-CoA carboxylase, which catalyzes the first committed step in fatty acid synthesis. Herein, we report the 2.6 Å resolution crystal structure of moiramide B bound to carboxyltransferase. An unanticipated but significant finding was that moiramide B bound as the enol/enolate. Crystallographic studies demonstrate that the (4S)-methyl succinimide moiety interacts with the oxyanion holes of the enzyme, supporting the notion that an anionic enolate is the active form of the antibacterial agent. Structure–activity studies demonstrate that the unsaturated fatty acid tail of moiramide B is needed only for entry into the bacterial cell. These results will allow the design of new antibacterial agents against the bacterial form of carboxyltransferase.